Pengembangan Instrumen Tes Kemampuan Berpikir Spasial Bagi Siswa SMA - Muhammad Aliman; Tuti Mutia; Dahri Hi Halek; Rafika Hasanah; Hujairah Hi Muhammad (Geodika: Jurnal Kajian Ilmu dan Pendidikan Geografi, 2020)
The competency that high school students need to have to study geography is spatial thinking ability. This ability was used as a basis to face global competition during the industrial revolution of 4.0. To understand the spatial thinking ability of high school students requires instruments that can measure in detail the abilities. This study aimed to determine the validity of questions consisted of reliability, discrimination power, level of difficulty and correlation between items of spatial thinking ability test for high school students. This research used a quantitative descriptive method that analysed using ANATES software. Based on the data analysis, the results obtained that the test instruments of spatial thinking ability can be used optimally because the discrimination power of the questions and the level of the question of difficulty worked correctly. However, the ability of instruments to discriminate the level of spatial thinking ability among students did not work maximally. Continuous development is needed to test these instruments so that this was able to measure in detail of spatial thinking skills for high school students.